2011
DOI: 10.1111/j.1365-2850.2011.01822.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse‐led delivery of specialist supportive care for bipolar disorder: a randomized controlled trial

Abstract: The aim of the study is (1) to assess the feasibility of delivering nurse-led specialist supportive care as an adjunct to usual care in the clinical setting; (2) to examine the relationship between the delivery of specialist supportive care and improved self-efficacy and functioning and reduced depressive symptoms. A randomized controlled trial of the clinical effectiveness of specialist supportive care as an adjunct to usual care was conducted in community mental health services at one site. Participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…There has also been a review that identified the potential effectiveness of social rhythm interventions and a qualitative study that identified that young people found the social rhythm component of IPSRT the most helpful in staying well . A previous feasibility study of delivering psychotherapy for BD in community mental services found that participants wanted it integrated and delivered by usual treatment team; and a commitment to a 9‐month therapy was unacceptable to many . In Christchurch, New Zealand, the median duration of treatment within community mental health services is 120 days, which is similar to findings from the United States showing that the median duration of acute mood episodes in BD is 13 weeks …”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…There has also been a review that identified the potential effectiveness of social rhythm interventions and a qualitative study that identified that young people found the social rhythm component of IPSRT the most helpful in staying well . A previous feasibility study of delivering psychotherapy for BD in community mental services found that participants wanted it integrated and delivered by usual treatment team; and a commitment to a 9‐month therapy was unacceptable to many . In Christchurch, New Zealand, the median duration of treatment within community mental health services is 120 days, which is similar to findings from the United States showing that the median duration of acute mood episodes in BD is 13 weeks …”
Section: Introductionmentioning
confidence: 66%
“…It is anticipated that it can form the basis for the ongoing engagement between the clinician and the patient. The intervention needs to be feasible, acceptable and fit with the local context: The manual developed in the United States required adaptation for the New Zealand setting and has been modified while maintaining the key principles. A previous feasibility study in the local context found that participants wanted the intervention integrated into usual care and delivered by their usual treatment team. The duration of the intervention is potentially feasible given the average length of stay in this community mental health service (120 days).…”
Section: Resultsmentioning
confidence: 99%
“…Depression and mania symptoms were assessed using the SCL-90, and there were no differences in changes in these measures over time between the two groups. Notably, this study was powered to detect relatively large effect sizes (>0.7), which suggests the possibility of type II error (31). …”
Section: Resultsmentioning
confidence: 97%
“…In all but one trial (27), psychotherapy was administered as an adjunct to pharmacologic treatments. In most cases, the addition of psychotherapy to pharmacotherapy was associated with improved outcomes for bipolar disorder compared with the control condition [but for exceptions, see, Scott et al (28), Meyer and Hautzinger (29), Parikh et al (30), Crowe et al (31), and de Barros Pellegrinelli et al (32)]. Below we briefly describe individual and group models of psychotherapy tested for bipolar disorder and the evidence supporting their efficacy/effectiveness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation